Nestin affects fusion pore dynamics in mouse astrocytes. (7th November 2019) - Lasič, Eva; Trkov Bobnar, Saša; Wilhelmsson, Ulrika; de Pablo, Yolanda; Pekny, Milos; Zorec, Robert; Stenovec, Matjaž
Abstract: Aim: Astrocytes play a homeostatic role in the central nervous system and influence numerous aspects of neurophysiology via intracellular trafficking of vesicles. Intermediate filaments (IFs), also known as nanofilaments, regulate a number of cellular processes including organelle trafficking and adult hippocampal neurogenesis. We have recently demonstrated that the IF protein nestin, a marker of neural stem cells and immature and reactive astrocytes, is also expressed in some astrocytes in the unchallenged hippocampus and regulates neurogenesis through Notch signalling from astrocytes to neural stem cells, possibly via altered trafficking of vesicles containing the Notch ligand Jagged‐1. Methods: We thus investigated whether nestin affects vesicle dynamics in astrocytes by examining single vesicle interactions with the plasmalemma and vesicle trafficking with high‐resolution cell‐attached membrane capacitance measurements and confocal microscopy. We used cell cultures of astrocytes from nestin‐deficient ( Nes −/− ) and wild‐type (wt) mice, and fluorescent dextran and Fluo‐2 to examine vesicle mobility and intracellular Ca 2+ concentration respectively. Results: Nes −/− astrocytes exhibited altered sizes of vesicles undergoing full fission and transient fusion, altered vesicle fusion pore geometry and kinetics, decreased spontaneous vesicle mobility and altered ATP‐evoked mobility. Purinergic stimulation evoked Ca 2+ signalling that was slightly attenuated in Nes −/− astrocytes, which exhibited more oscillatory Ca 2+ responses than wt astrocytes. Conclusion: These results demonstrate at the single vesicle level that nestin regulates vesicle interactions with the plasmalemma and vesicle trafficking, indicating its potential role in astrocyte vesicle‐based communication.